Ln(8) (Ln = Gd, Ho, Er, Yb) Butterfly core-exhibiting magnetocaloric effect and field-induced SMM behavior for Er analouge - Bala, Sukhen; Adhikary, Amit; Bhattacharya, Sudeshna; Sen Bishwas, Mousumi; Poddar, Pankaj; Mondal, Raju (ChemistrySelect, 2017)
In this article, we report four pyridyl-pyrazolyl based poly-nuclear cluster complexes with Ln(8) {Ln = [Gd-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(2)(MeOH)(1), [Ho-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](2), [Er-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(H2O)(3), [Yb-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(4) [DEA = Diethanolamine] cores. The impetus for this study was to explore the magnetic behaviour of lanthanide ions which are often ignored or overlooked. X-ray crystal analysis show that these complexes are isostructural and exhibit an interesting butterfly like topology. The semi-rigidity and asymmetric nature of the ligand led to different coordination environment around the metal centres. The lanthanide ions adopt two types of geometry, a bicapped trigonal prism and a distorted square antiprismatic geometry around the metal center. Such dissimilar coordination environments around the lanthanide centre can have profound effects on their magnetic behaviour. Indeed, the magnetic measurements revealed significant magnetocaloric effect for octanuclear gadolinium complex 1 with magnetic entropy change (-Delta S-m ) of 31.4 J kg(-1) K-1 for Delta H = 9 T at T = 3 K whereas Er analogue complex 3 displayed SMM behavior.